Lei anticorrup????o e partidos pol??ticos - Capelari Junior, Osvaldo (2017)
This study is dedicated to the application of the Brazilian anti-corruption law to political parties. Political parties are the mediators of the will of civil society and the state and, because of that, have a constitutional status of their own. They are indispensable to democracy. However, the behavior of the people exercising public functions creates risks of acts of corruption. This is the reason why the anti-corruption law elects objective, civil and administrative responsibility, with the purpose of sanctioning the legal entity of private law that competes or benefits from the act adversely affecting the Public Administration, including the foreign one. From the analysis of the anti-corruption law it is observed, although, that political parties were subtracted from their scope of incidence. It is important to point out that this is in line with the democratic ideal and, consequently, with a good democracy. This calls for responsiveness and accountability, and it is unreasonable for partisan associations to benefit from rules that draw the amount of enforcement from control agencies. On the other hand, since the political parties are contemplated in the law, due to the exegetical effort, one of the challenges of the present research, it is imperative that norms of good governance be created through independent internal control in order that the legal norms are and other regulations that may be created in its Statutes. In any case, the political party may, despite being considered not to be within the law, create integrity mechanisms, which will surely confer trust to the voter. This should be honored in the electoral campaign and his preferences be freely expressed in the vote. Yet, since democracy is not confined to voting, the role of accountability must be emphasized as fundamental to good party practices and, therefore, to the integrity of electoral and partisan systems. In this way, democracy will be substantive and the strengthening of political parties is one of its foundations.